Mid thoracic syndrome in pregnancy: a rare cause of secondary hypertension. (16th November 2010) - Johnson, SN; Kelleher, T; Neill, SO; Crean, P; Cosgrave, J; Meaney, J; Astbury, K; Regan, C; Byrne, B
Abstract : Severe secondary hypertension in pregnancy can be complicated by maternal intracerebral haemorrhage, cardiac or renal failure, superimposed pre-eclampsia, maternal death and fetal spontaneous abortion or perinatal death. The authors present the case of a 17 year old girl with no previous medical or surgical history, who booked for antenatal care at 15 weeks with a BP of 215/110 mm Hg equal in both arms and no palpable femoral pulses. Limited imaging revealed stenosis of the lower thoracic and abdominal aorta with lower limb and pelvic circulation provided by extensive collaterals between the internal mammary and inferior epigastric vessels. She was admitted to hospital at 19 weeks gestation for BP control and was managed medically as an inpatient until delivery of a healthy baby boy by caesarean section at 30 weeks which was precipitated by uncontrollable hypertension. Uteroplacental circulation was satisfactory despite marked lower limb hypotension evidenced by normal uterine and umbilical artery Doppler studies and serial growth estimation. Birth weight was 1.4Kg which was just below the 50 th centile for gestational age. Management involved a multidisciplinary team of obstetricians, cardiologists, vascular surgeons, anaesthetists and radiologists. Challenging issues in her care included (1) The risk of continuing with the pregnancy, (2) Vascular imaging was limited by pregnancy, (3) The role of vascular surgery that is stenting or surgical correction of the defect, (4) Medical management of severe hypertension in pregnancy, (5) Fetal surveillance and timing of delivery. These issues will be discussed in the presentation.